Dependence of severe storm occurrence on circulation types in Poland - Łupikasza, Ewa; Bielec-Bąkowska, Zuzanna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The paper investigates the relationships between the occurrence of thunderstorms with heavy precipitation (> 30 mm) and atmospheric circulation types. The study covers the period 1951–1998 and is based on a matching span of records of thunderstorm occurrence and daily precipitation totals at 47 weather stations in Poland. A catalogue of circulation types by Osuchowska-Klein, data on frequency of fronts over south-eastern Poland by Niedźwiedź and weather maps were used. In Poland, days with a thunderstorm and more than 30 mm of precipitation are extremely rare and occur mainly in summer. Their recurrence period amounts to about two to four years, with the exception of mountain areas (southern Poland) where they occur nearly every year. The heaviest precipitation on a day with thunderstorm, 166.1 mm, was recorded at a high-mountain station on Mt. Kasprowy Wierch. Apart from this station the highest precipitation was 141.0 mm and only eight stations had at least one record of more than 100 mm. Four regions characterised by different circulation types most favourable for the occurrence of thunderstorms with heavy precipitation were identified. In all of them southerly advection was most favourable for the occurrence of the phenomena studied (Sc, SEc, Sa/c), but that effect was especially prominent in the south-western region. Most of the days with thunderstorm and heavy precipitation coincided with the passing of an atmospheric front over Poland (53.8–81.9% days depending on the station). Days with air-mass thunderstorm and heavy precipitation were rare and mostly occurred in areas of variable topography.
Keywords: thunderstorm; heavy precipitation; atmospheric circulation; Poland